(Dinitrogen)molybdenum Complexes Supported by Asymmetric Silicon‐Centered Tripod Ligands: Steric and Electronic Influences on the Coordination of Mono‐ and Diphosphine Coligands. Issue 22 (4th July 2014) - Broda, Henning; Krahmer, Jan; Tuczek, Felix
Abstract: A reliable and generally applicable synthetic route for the rational synthesis of silicon‐centered tripod ligands with mixed dialkylphosphine/diarylphosphine donors is developed. On the basis of this protocol, two new asymmetric SiPPP′ ligands, SiP Me 2 P Ph and SiP Me 2 P i Pr, were prepared and employed for the synthesis of (dinitrogen)molybdenum complexes of the types [Mo(N2 )(SiPPP′)(P2 )] [P2 = (diphenylphosphino)methane (dppm), (dimethylphosphino)methane (dmpm), or two PMe2 Ph] and [Mo(N2 )2 (SiPPP′)(PMe2 Ph)]. The constitution of the complexes is elucidated by 31 P NMR spectroscopy and analyzed on the basis of steric and electronic factors. The activation of N2 in the synthesized dinitrogen complexes is determined by IR spectroscopy and correlated with the donor/acceptor properties of the phosphine coligands. Abstract : A synthetic route to silicon‐centered mixed dialkylphosphine/diarylphosphine tripod ligands has been established leading to nine new Mo–N2 complexes. The resulting structures and the activation of the coordinated N2 ligands are discussed with respect to steric and electronic effects.